2020
DOI: 10.3390/app10175887
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Tomato and Peduncle Location System Based on Computer Vision for Use in Robotized Harvesting

Abstract: Protected agriculture is a field in which the use of automatic systems is a key factor. In fact, the automatic harvesting of delicate fruit has not yet been perfected. This issue has received a great deal of attention over the last forty years, although no commercial harvesting robots are available at present, mainly due to the complexity and variability of the working environments. In this work we developed a computer vision system (CVS) to automate the detection and localization of fruit in a tomato crop in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…In recent years, machine learning, and especially deep learning, techniques in fruit detection has been increasingly used and tested [8,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Unlike conventional methods, machine learning is a more robust and accurate alternative with a better response to problems such as occlusion and green tomato detection.…”
Section: State-of-the-art 21 Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent years, machine learning, and especially deep learning, techniques in fruit detection has been increasingly used and tested [8,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Unlike conventional methods, machine learning is a more robust and accurate alternative with a better response to problems such as occlusion and green tomato detection.…”
Section: State-of-the-art 21 Literature Reviewmentioning
confidence: 99%
“…These challenges become greater in the early ripening stages, due to the high colour correlation between leaves and tomatoes. Despite this fact, the most common and relevant research found in the literature considers the harvesting period in the late maturation stage of tomatoes (where the tomato is already red), so the colour is therefore a feature used recurrently to differentiate the objects to be detected [15][16][17][18][19][20]24,34]. Considering the case of fruit detection and segmentation, the authors try to distinguish it from everything external and the background, which at the crop level, can be very complex.…”
Section: State-of-the-art 21 Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Precision agriculture can provide useful information in the early stage to enable better decision making on the management system. In recent years, computer vision and artificial intelligence technology have developed to meet the growing demand for fast and accurate grain crop production [ 1 , 2 ]. As reviewed by a previous study [ 3 ], machine learning techniques have been widely used for the early and precise detection of biotic stress in the crop, specifically for the detection of weeds, plant diseases, and insect pests.…”
Section: Introductionmentioning
confidence: 99%